The impact of different competitive environments on pacing and performance - Konings, M. J.; Hettinga, F. J. (International Journal of Sports Physiology and Performance, 2018)
Purpose: In real-life competitive situations, athletes are required to continuously make decisions about how and when to invest their available energy resources. This study attempted to identify how different competitive environments invite elite short-track speed skaters to modify their pacing behavior during head-to-head competition. Methods: Lap times of elite 500-, 1000- and 1500-m short-track speed skating competitions between 2011 and 2016 (N?=?34,095 races) were collected. Log-transformed lap and finishing times were analyzed with mixed linear models. The fixed effects in the model were sex, season, stage of competition, start position, competition importance, event number per tournament, number of competitors per race, altitude, and time qualification. The random effects of the model were athlete identity and the residual (within-athlete race-to-race variation). Separate analyses were performed for each event. Results: Several competitive environments, such as the number of competitors in a race (a higher number of competitors evoked most likely a faster initial pace; coefficient of variation [CV]=1.9-9.3%), the stage of competition (likely to most likely, a slower initial pace was demonstrated in finals; CV=-1.4% to 2.0%), the possibility of time qualification (most likely a faster initial pace; CV=2.6-5.0%), and competition importance (most likely faster races at the Olympics; CV=1.3-3.5%), altered the pacing decisions of elite skaters in 1000- and 1500-m events. Stage of competition and start position affected 500-m pacing behavior. Conclusions: As demonstrated in this study, different competitive environments evoked modifications in pacing behavior, in particular in the initial phase of the race, emphasizing the importance of athlete-environment interactions, especially during head-to-head competitions